The sharing Powers in the Constitution of Federal States: The Applicability of Decentralization - Hassan, Ali Tawfiq; Salih, Namam M.; Shareef, Amera Jaafar (Eximia, 2022)
This paper focuses on the applicability of federal system as a legal-political means in providing Minorities Rights and managing the relationship among various constituent groups as a real foundation of decentralization principle in sharing powers between constituent units. The federal system can be realized through the establishment of federal constitutions. We exemplify Iraq as a federal model of multi-culturalism state that accommodating with new development of democratic principles, which associate with diversity and decentralization in sharing power. The Iraqi constitution is approved through referendum, the Kurdistan population is also participated in this referendum, where the Kurdistan entity and equality among its national and religious components has been de jure recognized. Article 117(1) identify the Kurdistan as a sovereign federal unit enjoying legal-political competences. The study suggests a legal solution to minimize the conflicts between Iraqi entities, legal approach to resolve the ambiguity in several articles: 112(1), 116, 117(2), and 140(2).